The Implementation of Wattpad-Based-Digital Reading in Senior High School Student - Andi Asti Ahyandhita; Muhammad Tahir; Vivit Rosmayanti (Program Studi Magister Pendidikan Bahasa Inggris, Fakultas Bahasa dan Sastra- Universitas Negeri Makassar., 2026)
Reading comprehension remains an essential issue for Indonesian EFL students, especially because they don't pay much attention in regular reading classes. Combining digital reading platforms may be a way to increase students' engagement in reading. The purpose of the research was to examine learners' engagement in reading comprehension through Wattpad-based digital reading. A pre-experimental quantitative research design was used involving twelfth-grade students from SMA Negeri 1 Bulukumba. This investigation took place in October and November of 2025. Data were collected using a Likert-scale questionnaire filled out following students' engagement in Wattpad-based reading activities. The questionnaire looked at five dimensions of engagement: emotional, behavioral, participation, cognitive, and skills engagement. The data is described by turning responses into percentages to find patterns in how students engage. The findings demonstrated that high levels of emotional engagement, indicated by increased interest, excitement, and satisfaction in reading activities. Cognitive engagement was also high because students understood the texts, linked what they read to what they already knew, and used concepts in real-life situations. Participation engagement worked well since students were actively talking about Wattpad stories. Students' independent reading habits and usage of active reading strategies showed that they were engaged in skills. However, behavioral engagement had only minimal outcomes, especially when it came to consistently finishing longer readings. The study finds that digital reading on Wattpad efficiently promotes multidimensional student engagement in reading comprehension. It is suggested that English teachers include digital reading platforms in their education while offering suitable supervision to improve students' reading consistency and improve engagement outcomes.